PENGARUH KOMUNIKASI, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL BALIKPAPAN - Alfaridzi, Muhammad Fatahilla; Anam, Syahril; Yuliani, Tutik; Hendrawan, Yudhi (MEDIA RISET EKONOMI [MR.EKO], 2025)
The purpose of this study was to determine the Influence of Communication, Motivation, and Work Discipline on Job Satisfaction of Employees at the Balikpapan Population and Civil Registration Service. The population in this study was 72 people and a sample of 45 people was taken using a purposive sampling technique using criteria determined by the author, namely permanent employees. The data analysis method used was Structural Equation Modeling based on PLS (SEM PLS) with the Smart-PLS application, taking into account the variables of Job Satisfaction, Communication, Motivation, and Work Discipline. The results of this study indicate that communication and motivation have a positive and significant influence on employee job satisfaction at the Balikpapan Population and Civil Registration Service, while work discipline has no effect on employee job satisfaction at the Balikpapan Population and Civil Registration Service.